Visual Chaos of the Formal Order of the University Buildings - Zainab Ibrahim Abbas (Iraqi Journal of Architecture and Planning, 2018)
This Paper Studies Visual Chaos phenomenon in the University of Technology, after thedevelopment and rehabilitation of its Buildings, Which was the reason for the absence of theformal order Unity of its Buildings. So the aim of this paper is to built a base Knowledge tovisual chaos phenomenon, Order and Formal Order. The research hypothesis was â€œthere is avisual chaos in the formal order of the elevations and the master plan of the Universityof Technologyâ€. The research defines the visual chaos as the absence of order in the formalpattern. The research has built a theoretical framework defined the visual chaos, and projectit, on a selected buildings that have been rehabilitated and a new project of the University ofTechnology. The main research findings was the absence of identity of the final productelevations, and the master plan of the University, which was the reason for the visual chaos ofthe formal order. The absence of planning and good design for the master plan and elevationswas the reason for ignoring the unity in the form and context. So the paper insist on finding arelation between old and new through investing elements and formal properties which createlegible context and unity in the order of the University